Restructuring Europe's armed forces in times of austerity: Challenges and opportunities for governments and industry - Sophie-Charlotte Brune; Alastair Cameron; Jean-Pierre Maulny; Marcin Terlikowsky (Stiftung Wissenschaft und Politik (SWP), 2010)
Current budgetary cuts are exerting strong pressure on defence ministries across Europe to reform their armed forces and the way they do business. A look at the situations of Germany, the United Kingdom, France and Poland reveals that policy responses, to date, have remained largely confined to the national or bilateral level. Instead, co-ordinating restructuring efforts and exploiting the options of pooling and sharing capabilities would enhance the potential of European armed forces. For that to happen, policymakers in the EU need to overcome an apparent fatigue with intra-European multilateral co-operation. Against this background, we explore what concrete policy options are on the table to achieve savings whilst pursuing much needed structural reforms of the armed forces and strengthening a European Defence Technological and Industrial Base (EDTIB)
Keywords: 320